ECOPRINT TRAINING FOR WOMEN EMPOWERMENT IN NGEMBAT SUB-VILLAGE, MOJOKERTO - Aniendya Christianna; Heru Dwi Waluyanto; Ani Wijayanti Suhartono (Institute of Research and Community Outreach - Petra Christian University, 2019)
The number of women in Ngembat sub-village is quite large, both from adolescence to the elderly, but most of them are only housewives who are not economically productive. Everything depends on the husband who works as a farm laborer and builder. Women in Ngembat sub-village have a lot of free time that can be used for productive activities. The ecoprint training held during the Community Outreach Program (COP) is the development of DKV 4 courses that implement creative-sociopreneurship learning. This subject emphasizes the aspects of entrepreneurship in the field of creative industries by utilizing local strengths. Natural resources that exist around Ngembat sub-village can be utilized as products of economic value. Abundant teak leaves due to the vast size of teak forests can be a source of income for women on the sidelines of carrying out their domestic duties in the household. Free time while waiting for children to come home from school and their husbands from work can be used to empower themselves by producing creative products and economic value. Thus, not only does women's knowledge and skills improve, but the family economy can also improve